2018
DOI: 10.1051/e3sconf/20182801012
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental measurement of odour nuisance in city agglomeration using electronic nose

Abstract: Abstract. The paper describes an operation principle of odour nuisance monitoring network in a city agglomeration. Moreover, it presents the results of investigation on ambient air quality with respect to odour obtained during six-month period. The investigation was carried out using a network comprised of six prototypes of electronic nose and Nasal Ranger field olfactometers employed as a reference method. The monitoring network consisted of two measurement stations localized in a vicinity of crude oil proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…At two biogas plants (A and F), a similar impact is observed of mean air humidity on c od and i od compared to the effect presented in the literature [35,36]-a higher c od and i od at lower air humidity. However, this relationship is observed in the case of differences in air humidity at a minimum level of about 20%.…”
Section: Impact Of Air Temperature and Humidity And Technological Factors On Odour Concentration And Intensity: Analysessupporting
confidence: 80%
See 2 more Smart Citations
“…At two biogas plants (A and F), a similar impact is observed of mean air humidity on c od and i od compared to the effect presented in the literature [35,36]-a higher c od and i od at lower air humidity. However, this relationship is observed in the case of differences in air humidity at a minimum level of about 20%.…”
Section: Impact Of Air Temperature and Humidity And Technological Factors On Odour Concentration And Intensity: Analysessupporting
confidence: 80%
“…The device used in the study was the olfactometer Nasal Ranger ® (St. Croix Sensory, Inc., Stillwater MN, USA]). Odour concentrations in every measurement point were calculated based on two readings of the D/T parameter (dilution-to-threshold ratio), using the following formulas [2,31,35,39,40]:…”
Section: Study Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The research also covered odour measurements, including determination of odour intensity by means of sensory assessment on a six-level scale (0-5), where "0" means "no odour", and "5" means "very strong odour", and measurement of the multitude of dilution of contaminated air with treated air (D/T -dilution to threshold) by means of a dynamic olfactometer Nasal Ranger (St. Croix Sensory, Inc.; Stillwater [Minnesota, USA]). Based on the known parameter D/T, odour concentrations were calculated at each of the study receptors [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
“…Authors concluded that comparing the price of both e-noses the home-made one exhibits a satisfactory level of correct results as compared to much more expensive Heracles Neo. As suggested by the same authors [193] the performance of e-nose based on gas sensors can be improved by implementation of more and more sensitive sensing arrays. Presented above applications are summarized in Table 8.…”
Section: Application Of the Electronic Noses For Odor Impact Assessme...mentioning
confidence: 96%